“Negation, Annihilation and Nothingness”: Risks and Recovery from Parental Loss and Abandonment in Nancy Huston’s Instruments of Darkness - Schaub, Danielle (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2012)
Nancy Huston’s Instruments of Darkness illustrates how the narration of trauma has at once potentially redeeming and devouring powers. A joint literary-psychoanalytic exploration of the main characters’ childhood experiences and subsequent severed and severing links/bonds highlights how the text bears the mark of past traumas, reflecting the theories of LaCapra, Bion, D. W. Winnicott, Laub, Poland, and André Green. Following the multiple processes through which the protagonist of the framing narrative fights against her past while recording the loops of the protagonist’s life in the framed narrative, the novel engages in a therapeutic process counteracting the traumatic impact of a dead mother, whether physically or psychically.